FEATURES OF THE HYPERTENSIVE HEART DEVELOPMENT IN MINEWORKERS WITH ARTERIAL HYPERTENSION - Sheiko, S.О.; Kolb, N.О. (World of Medicine and Biology, 2019)
The purpose of the research project was to study the clinical and structural-functional features of hypertensive heart (HH) in miners with arterial hypertension (AH) with experience of over 10 years and to develop clinical and functional criteria for its diagnosis. The examined mineworkers included 127 underground miners and 58 surface profession workers aged 35-55 years, with experience in mining conditions exceeding 10 years, with normal high blood pressure (AP), stages І and ІІ hypertension, which constituted respectively the main and the auxiliary groups. The total of 30 virtually healthy men, who did not work under harmful conditions, made control group 1, and 30 practically healthy miners of superficial occupations formed the control group 2. The general-clinical examination of patients, electrocardiography (ECG), daily monitoring of blood pressure were carried out. The structural and functional heart status was studied using one-and two-dimensional echocardiography (ECHO-CG) by means of “PHILIPS-HDI 1500” apparatus according to the standard procedure. The types of left ventricle (LV) geometry according to Framingham criteria were studied. The methodological approach to studying the LV weight was based on the Devereux formula (Pen Convention). The examination data testify to the predominant development of concentric remodeling in healthy miners, and in 25.2% of them - the physiological left ventricular hypertrophy (LVH). Unlike pathological LVH, the physiological “working” LVH is not accompanied by the formation of diastolic dysfunction of the LV (LVDD). In 98.5% of the miners there is a concentric structural-functional type of hypertensive heart, based on the development of concentric LVH and the concentric LV remodeling. In 14.7% of the main group miners with the II stage hypertensive disease (HD), the right ventricle hypertrophy develops. The peculiarity of hypertensive heart in miners of underground jobs is its development against the background of the physiological “working” LVH. The following types of LV remodeling are prevalent in miners: concentric left ventricular hypertrophy (86.2%) and concentric remodeling (12.3%). At the early stages of the hypertensive heart development, the left ventricular diastolic dysfunction is formed in miners, which at later stages is transformed into diastolic heart failure with the subsequent attachment of systolic heart failure. In miners with hypertensive heart, the structural-functional status of the right ventricle undergoes early disorders, which is manifested by diastolic dysfunction.
Keywords: arterial hypertension; hypertensive heart; left ventricle remodeling